2020
DOI: 10.17977/jptpp.v5i2.13187
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kompetensi Mengembangkan RPP melalui Lesson Study bagi Guru SD Laboratorium

Abstract: <pre><strong>Abstrack:</strong> This School Action Research aims to uncover and describe teacher competencies in developing Lesson Plans, and implementing lesson studies. This SAR was designed with the Mc Taggart's classroom action research design in two action cycles. The research subjects were 11 elementary school teachers. The research instrument was developed by researchers in the form of work tables 1-5 to collect teacher competency data designing 10 components of lesson plans, and field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…Teachers are dedicated to mastering the theories and principles of learning by carrying out varied learning activities and choosing the right methods to increase participants' learning motivation. This view is in line with the opinion expressed by Solihin (2016) that applying learning theory by choosing the right method.…”
Section: Mastering Learning Theory and Educational Learning Principlessupporting
confidence: 83%
“…Teachers are dedicated to mastering the theories and principles of learning by carrying out varied learning activities and choosing the right methods to increase participants' learning motivation. This view is in line with the opinion expressed by Solihin (2016) that applying learning theory by choosing the right method.…”
Section: Mastering Learning Theory and Educational Learning Principlessupporting
confidence: 83%
“…The fact that there are activities in each cycle to meet in developing, executing, and performing evaluations together within a few months, capable of producing better learning, and lesson study can enhance teacher competency, is also supported by earlier research (Supriyanto et al, 2020;Annisa et al, 2021). Referring back to earlier study, Seleznyov (2018) found that the method of implementing lesson study in Japan is inextricably linked to the cooperative actions of teachers in lesson planning and reviewing activities that have been used in the teaching and learning process.…”
Section: Ijels 11(2):87-91mentioning
confidence: 86%
“…SEM is an integrated approach between data analysis and concept construction. In SEM, researchers can carry out three activities simultaneously, namely checking the validity and reliability of instruments (equivalent to confirmatory factor analysis) and obtaining relationship models that are useful for estimation (equivalent to structural models or regression analysis) [29]. SEM from the AMOS7 statistical software package can be used in modeling and hypothesis testing.…”
Section: Conceptual Frameworkmentioning
confidence: 99%